Addressing medical needs of adolescents and adults with autism spectrum disorders in a primary care setting. (January 2018) - Saqr, Youssra; Braun, Erika; Porter, Kyle; Barnette, Debra; Hanks, Christopher
Little has been reported about how to improve health care access and delivery for adolescents and adults with autism spectrum disorder. To understand the contributions to the health disparities in the autism spectrum disorder population, we conducted two independent research approaches to learn about current medical needs. A retrospective chart review was performed to evaluate medical comorbidities and medication use. A focus group was also created to address barriers faced in providing medical care. Of 126 charts reviewed, 49% (n = 62) had intellectual disability, 49% (n = 62) had attention-deficit hyperactivity disorder, 52% (n = 65) had anxiety, 41% (n = 52) had obesity, 31% (n = 39) with a history of aggressive behavior, 31% (n = 31) had depression, 22% (n = 28) had seizures, and 9% (n = 11) had hypertension. A Medical Regimen Complexity Index score was determined to examine medication use trends in the autism spectrum disorder population. Medical Regimen Complexity Index scores were significantly higher for patients with intellectual disability, patients with seizures, and patients with a history of aggressive behavior. Both the focus group and our pre-visit assessment identified the waiting room and waiting time as barriers to care. Understanding the comorbidities, polypharmacy, and medical barriers should provide a better understanding of the current health care access and delivery needs of adolescents and adults with autism spectrum disorder.